Kreativitas Guru dalam Menggunakan Metode Pembelajaran SKI di MIN 1 Medan - Nasution, Abdul Gani Jamora; Simanjuntak, Andini Zahara; Siambaton, Nur Hafni Bahri; Farisi, Muhammad Al (Al-DYAS, 2023)
The purpose of this study was to find out how the creativity of teachers in implementing Islamic Cultural History (SKI) learning. The results of the study found that teachers at the Medan MIN 1 school still used the lecture method in carrying out SKI learning and students said that they felt bored listening to the material that had been delivered by the teacher, especially since there was too much material or studies that the teacher had delivered. To overcome this, the teacher uses the cooperative learning method. Students are expected to be able to study in a group and carry it out together. In cooperative learning (cooperative learning) students are trained to work together in a group. The important point in this method is that students are expected to be able to work together in a team. Students who understand are asked to focus on becoming peer tutors.